If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 4(-3) + -3 Multiply 4 * -3 9 = -12 + -3 Combine like terms: -12 + -3 = -15 9 = -15 Solving 9 = -15 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -14(-10x-13)=1162 | | -24+7x=25 | | 2x22/7x25x3.5 | | 4x^6+11x^5-x^3+7x+7=0 | | 3x-6(6x+31)=12 | | 2*x=512 | | 1/10_=k/100 | | 3x-4+9x=10 | | 2x+y^2=36 | | (x+9)+(4x^2)=0 | | 5x+1=8x-32 | | 5/9x31/90 | | (f+g)(x)=(x+9)+(4x^2) | | 20+5x=10-8x | | 11.5=14t+20.6 | | 21x+3y=210 | | x^2=-192 | | 30x^3+26x^2+4x= | | x-1/3=12 | | 6x+3x=3x-x | | x/2-3-x≥1 | | 4/(-2-8i) | | 9a+10=64 | | 3x+4.8=12 | | 4(x-7)=6(x-9)+60 | | 1x+2y=60 | | N/24=4/9 | | 0.7xX=29820 | | 8-0.03w=1.8 | | 3(x+4)=x-3 | | 3v+13=40 | | M^2=-49 |